2011
DOI: 10.1002/jmri.23502
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of MRI to ultrasound in the diagnosis of fetal anomalies

Abstract: Purpose: To evaluate the contribution of MRI to ultrasound (US) in the diagnosis of fetal anomalies. Materials and Methods:After informed consent and institutional review board approval, concomitant US and MR imaging were performed for 184 fetuses with suspected anomalies in university hospital. Postnatal final diagnoses were obtained for 183 anomalies in 151 fetuses either by radiological examination, surgery, autopsy, or inspection. The prenatal US and MR diagnoses were compared with respect to postnatal dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 30 publications
(38 reference statements)
1
50
0
1
Order By: Relevance
“…For these reasons, magnetic resonance imaging (MRI) examination has been proposed by some authors. 30,31 This procedure, without using ionizing radiation has been demonstrated to be safe for the foetus. Moreover it has excellent tissue contrast, exam results are not operator-dependent and it is not infl uenced by external factors such as obesity of the mother or oligohydramnios.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For these reasons, magnetic resonance imaging (MRI) examination has been proposed by some authors. 30,31 This procedure, without using ionizing radiation has been demonstrated to be safe for the foetus. Moreover it has excellent tissue contrast, exam results are not operator-dependent and it is not infl uenced by external factors such as obesity of the mother or oligohydramnios.…”
Section: Discussionmentioning
confidence: 94%
“…However, it is still unclear what effect MRI has on the developing foetus; for this reason, some authors argue that offering MRI as routine examination is not justifi ed. 13,30 Although idiopathic in the majority of cases, clubfoot could be sometimes associated with chromosomal abnormalities, genetic syndromes or other deformities. Historically, a sonographic diagnosis of clubfoot was considered an indication for amniocentesis, though recent studies have suggested karyotyping only if associated anomalies on the sonographic survey are presents.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were, however, criticized for their inherent biases, such as their retrospective nature, skill of ultrasound examiners, and time lapse between ultrasound and MRI that may allow for some in utero evolution of the lesions. Prospective studies were designed to overcome these limitations, and the results still suggested that MRI can provide additional information that lead to changes in clinical management for fetuses with either intra or extracranial anomalies [23,24]. Obstetric conditions where MRI may provide additional information of clinical significance are summarized in Table 2.…”
Section: Indications Of Fetal Mrimentioning
confidence: 99%
“…There were 44% ultrasound and 25% MRI examinations disagreement with postnatal diagnosis [27]. The MRI can either reverse the diagnosis or discover additional CNS findings in up to 55% of fetuses with borderline ventriculomegaly [24]. Figure 1 shows the difference in visual inspection of fetal brain from an ultrasound and MR image.…”
Section: Fetal Central Nervous System Anomalies and Functional Neuroimentioning
confidence: 99%
“…Im Schädelbereich hat sich die fetale MRTDiagnostik als Ergänzung fest etabliert [3]. Bei be- ren Anomalien ist die Datenlage noch zu unsicher und kasuistisch, um über den diagnostischen Mehrgewinn des MRT eine Aussage treffen zu können [4].…”
unclassified